A técnica da descrição em catálogos e bibliografias: contribuição aos fundamentos da catalogação - Vinicius de Souza Tolentino (2015)
In the course of each epoch, the human knowledge production, presented in different holders and diverse technology. The product of this activity received influence of theory approaches and since the twenty century, document with the meaning of cultural object, began to be usewith more frequency. The document, generated by exchange between human, by the language, in the context of a certain culture, is comprehend while form and content, and its representation is worked from many levels of meaning production in the context of information systems. The documentary products from information systems are results ofprocess influenced by a set of knowledge and ability developed by technical activities of information organization that takes in account historical conditioned institutional aspects. This research discuss a specific process of information organization description , theconstitution of it is the set of procedures that stand for document identification. Thus, it proposes to explore the construction of technical description in catalog and at bibliography, with the aim to contribute to a discussion about the theory fundament of Cataloguing. Considering information systems can have different objectives like archival, museologic and bibliography the description is work under last approach. The research development is justified by a perception of technology incorporated to Cataloguing studies and have influenced, in a mechanistic form, the teach on Brazilian undergraduate courses onlibrarianship. We believe this study contribute to debate around questions on technique that are not confront on the major of Cataloguing. The research is drive by the bibliographic and documental method. Concludes pointing that the discussion about Cataloguing andBibliography is a significant contribution to a theory path about understand the production of diverse bibliographic repertories.